The Dynamics of Education on the Development of an Intellectual Citizenry in Africa - Munyaradzi A. Dzvimbo (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This article explores the importance of education and schooling precisely, as the catalyst for the development and transformation of citizens within, the African context. Historically, intellectual and citizenship education has always been seen as a western concept within the African continent. Hence, this exacerbated the myopic view that intellectual education is new as its approach in schools is often western oriented. Drawing from post-colonial theory, this study opines that though education and learning in particular have played a pivotal role in the enhancement and transformation of citizens in Africa as a whole during the post-independence era, citizenship education is not a new concept. Further, I expound and interrogate the African governments’ efforts and initiatives in fostering citizenship through learning. More so, this study points out that if we do move beyond any labelling essentialities, intellectualism has always been part and parcel of the nucleus of education among these nations and schools have also served as catalyst of social change. This is clearly reflected in various tasks and projects found in educational policies and frameworks which include enhancing the provision and access to education, language policies, indigenous knowledge systems and the indigenisation of the school curriculum  to enable it to be relevant to the current national ideals and vision. Conclusively, these programmes and initiatives were obviously implemented towards citizenship development aimed at empowering pupils with specific kind of education ideal for intellectual and national development within the countries of the Global South. Thus, the paper opines that the teaching of new learning areas through heritage studies in secondary schools, national and strategic studies in tertiary institutions should further be reconceptualised to reflect the local context and their ways of understanding and deconstructing the colonial narratives and mind set.